1984
DOI: 10.1097/00004032-198401000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Rainsplash As a Mechanism for Soil Contamination of Plant Surfaces

Abstract: We characterized the physical transport of soil, and therefore contaminants attached to the soil, onto vegetative surfaces due to rainsplash. Soil accumulation by tomato plants (Lycopersicon esculentum) was investigated as a function of soil particle size, rainstorm characteristics, foliage height, surface area and canopy cover of the plants. No soil particles greater than 105 micron in diameter were detected on the plants. Most of the soil was splashed no higher than 40 cm above the ground surface. Linear rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(40 citation statements)
references
References 0 publications
0
40
0
Order By: Relevance
“…Since raindrops have high kinetic energy they might remove many particles by splashing on impact with the leaf surface. Splashing is not only very effective in contaminating surfaces (Dreicer et al, 1984 ;Foster et al, 1985), but might also be an important factor in the removal of particles from smooth surfaces, as has been shown for the dispersal of fungal spores (Gregory, Guthrie & Bunce, 1959 ;Walklate, McCartney & Fitt, 1989). Especially heavy rain occurring during thunderstorms should be very effective in this respect, and might explain reasonably the decrease in contamination of beech leaves in later summer.…”
Section: Wettability and Contaminationmentioning
confidence: 97%
“…Since raindrops have high kinetic energy they might remove many particles by splashing on impact with the leaf surface. Splashing is not only very effective in contaminating surfaces (Dreicer et al, 1984 ;Foster et al, 1985), but might also be an important factor in the removal of particles from smooth surfaces, as has been shown for the dispersal of fungal spores (Gregory, Guthrie & Bunce, 1959 ;Walklate, McCartney & Fitt, 1989). Especially heavy rain occurring during thunderstorms should be very effective in this respect, and might explain reasonably the decrease in contamination of beech leaves in later summer.…”
Section: Wettability and Contaminationmentioning
confidence: 97%
“…Dreicer et al (1984) investigated the rain splash pathway for tomato plants and found that only finer soil particles were retained on plant surfaces. The octanol-air partition coefficient (K OA ) has been suggested as a suitable indicator of the significance of the dry deposition contamination pathway for semi-volatile organic chemicals (McLachlan 1999).…”
Section: Particulate Deposition On Plant Surfacesmentioning
confidence: 99%
“…[2] Broad, longstanding interest in rain splash of soil grains as an erosional process [Ellison, 1944;DePloey and Savat, 1968;Carson and Kirkby, 1972;Mosley, 1973;Sharma and Gupta, 1989;Sharma et al, 1991;Erpul et al, 2002Erpul et al, , 2008van Dijk et al, 2002;Gabet and Dunne, 2003;Legout et al, 2005;Furbish et al, 2007] and as a mechanism contributing to transport and dispersal of soil-borne pathogens, contaminants and nutrients [Dreicer et al, 1984;Wainwright et al, 1999;Bock et al, 2005;McGonigle et al, 2005] prompts the need for a unifying, and practical, description of rain splash transport that goes beyond [Dietrich et al, 2003] current semiempirical models. Recent success in clarifying the basic physics of the grain splash process [Furbish et al, 2007] allows us to formulate a description of grain motions, resulting from raindrop impacts, within the stochastic framework of the Master Equation [Risken, 1984].…”
Section: Introductionmentioning
confidence: 99%
“…Recent success in clarifying the basic physics of the grain splash process [Furbish et al, 2007] allows us to formulate a description of grain motions, resulting from raindrop impacts, within the stochastic framework of the Master Equation [Risken, 1984]. The result of this formulation is an advection-dispersion equation that (1) takes into account the highly intermittent activation of soil grains by raindrops; (2) reveals the soil-grain analogue of molecular diffusion; (3) highlights the role of slope-dependent grain drift and distinguishes it from Fick-like diffusion; (4) provides a framework for predicting dispersal of soil-borne substances [Dreicer et al, 1984;Bock et al, 2005;McGonigle et al, 2005]; and (5) clarifies how rain splash contributes to roughening [Jyotsna and Haff, 1997] of desert landscapes in association with variations in vegetation cover [Parsons et al, 1992;Bochet et al, 2000]. The formulation unambiguously clarifies, for the specific case of rain splash transport, the relation between grain-scale motions and the ''diffusion'' of topography as articulated by geomorphologists [Roering et al, 2002].…”
Section: Introductionmentioning
confidence: 99%